The Organizational Dimensions as a Determinant of Village Apparatus Knowledge Sharing Impacting Community Participation in Kerinci Regency - Faisal Amri; Ida Yusnita; Ayu Esteka Sari (Universitas Muslim Indonesia, 2022)
The rationale for village regulation is diversity, participation, genuine autonomy, democratization, and community empowerment. One of the main determinants of the above efforts' success is community participation in the entire village development process. This study aims to determine the organizational dimensions as a determinant of village apparatus knowledge sharing, impacting community participation in Kerinci Regency. We conducted this research in Kerinci Regency, Jambi Province. We Started the research from March 2020 to September 2020. The population in this study was the village apparatus in Kerinci Regency. This study's sampling method in this study was cluster sampling by grouping samples by region with a total sample size of 108 respondents. The data used in this study are primary data through interviews and a list of questions with a questionnaire. Analysis of the data in this study using a structural equation model with the analytical tool used is using AMOS. The results showed that the coefficient of determination of Knowledge Sharing's influence could explain by the organizational dimension variables of organizational culture, organizational structure, and training is 9.4%. Meanwhile, the coefficient of determination for the magnitude of community participation's influence, which can be explained by the organization's variable dimensions of organizational culture, organizational structure, training, and knowledge sharing, is 33.7%. This study resulted from testing the hypothesis that training positively and significantly affects Knowledge Sharing. Organizational structure, training, organizational culture, and knowledge sharing influence community participation.